The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1021/ic801427b
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous V(V)-Peroxo-Amino Acid Chemistry. Synthesis, Structural and Spectroscopic Characterization of Unusual Ternary Dinuclear Tetraperoxo Vanadium(V)-Glycine Complexes

Abstract: Vanadium participation in cellular events entails in-depth comprehension of its soluble and bioavailable forms bearing physiological ligands in aqueous distributions of binary and ternary systems. Poised to understand the ternary V(V)-H(2)O(2)-amino acid interactions relevant to that metal ion's biological role, we have launched synthetic efforts involving the physiological ligands glycine and H(2)O(2). In a pH-specific fashion, V(2)O(5), glycine, and H(2)O(2) reacted and afforded the unusual complexes (H(3)O)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 82 publications
1
18
1
Order By: Relevance
“…Given that these species bear a physiologically important moiety present in human fluids, it seemed important to investigate whether glycinate V(V)-peroxo species exhibits biological activity, [V 2 (O) 2 ( 2 :Á 2 :Á 1 -O 2 ) 2 (Á 2 -O 2 ) 2 (Gly)] (GlyH = glycine [180] , Fig. 4).…”
Section: Oxido-and Dioxido-vanadium(v) Speciesmentioning
confidence: 99%
“…Given that these species bear a physiologically important moiety present in human fluids, it seemed important to investigate whether glycinate V(V)-peroxo species exhibits biological activity, [V 2 (O) 2 ( 2 :Á 2 :Á 1 -O 2 ) 2 (Á 2 -O 2 ) 2 (Gly)] (GlyH = glycine [180] , Fig. 4).…”
Section: Oxido-and Dioxido-vanadium(v) Speciesmentioning
confidence: 99%
“…Since vanadium is a good nucleus for NMR, the formation of monoand dinuclear complexes was examined by 51 V NMR. The 51 V chemical shift of (II) was not given in the literature by Gabriel et al (2009), and an attempt to get 51 V signals under the conditions of pH in the range 4-7, a glycine/vanadium ratio in the range 0-4 and a H 2 O 2 /vanadium ratio of 2, indicated that a signal possibly assigned to (II) appeared at À710 p.p.m. at a pH range of 4-6 and a glycine/vanadium ratio in the range 1-4.…”
Section: Figurementioning
confidence: 96%
“…This is true also with more complicated, often polynuclear, structures: see, as just a few examples, complexes 10, 39 and related structures. [32][33][34]48,55 A review with a collection of salient UV-vis data for monoperoxo vanadium species recently appeared. 27 Quite different is the scenario of the 51 V-NMR chemical shifts, related data are collected in Table 2.…”
Section: Peroxo Vanadium Complexesmentioning
confidence: 99%